Bioactive membranes of polymeric micro and nanocomposites prepared with the natural anionic marine polysaccharide (Alginate) functionalized with extracts of cat’s claw (uncaria tomentosa) and aloe vera - Kim S. (2020)
In this research, the nanostructured alginate (AL) membranes were prepared with natural bioactive compound, Cat's claw (Uncaria tomentosa) extract (UT). UT is broadly used as an anti-inflammatory agent and the effect on the treatment of Rheumatism was proved by many scientists. For this reason, we added this bioactive compound in the process of AL membrane formulation to improve the biological activities. 2-dimentional (2-D) and 3-dimentional (3-D) AL membranes were prepared with and without addition of UT extracts. 3-D AL membranes were prepared using ultrasound with high intensity. The wettability of AL membranes depending on the concentration of AL was studied by measuring contact angle and surface energy. Stabilization agent, poloxamer 407, was used to improve the stability of AL nanoemulsion. The effects of UT in 3-D AL membranes were studied by measuring swelling behavior and contact angle. The surface morphology was measured with scanning electron microscopy (SEM). Comparing to 2-D AL membranes, 3-D AL membranes presented rougher surface due to AL nanoparticles presence. When UT was incorporated in AL membranes, strong antioxidant activity and higher contact angle and swelling ratio were observed than non-UT incorporated AL membranes. © 2020 Trans Tech Publications Ltd, Switzerland.